The Heritage of Latin classics incunabula in the “Marqués de Valdecilla” Historical Library (Complutense University of Madrid) (Minerva, 2019)
The aim of this paper is to present the incunabula by Latin authors (up to the 2nd century) kept in the “Marqués de Valdecilla” Historical Library, created with Cardinal Cisneros’s first acquisitions to develop his academic project. After a brief description of the library and the origin of its collection, detailed information of its incunabula, its origins, previous owners and printers will be offered, with an emphasis on some notable copies. All the information is then condensed in the tables which can be found in the Annex.
Keywords: incunabula; Latin classics; “Marqués de Valdecilla” Historical Library